The association between betel quid use and oral potentially malignant and malignant disorders in Southeast Asian and Pacific regions: a systematic review and meta-analysis with GRADE evidence profile - Jasim, Aula; Li, Xia; Octavia, Alfini; Gunardi, Indrayadi; Crocombe, Leonard; Sari, Elizabeth Fitriana (Frontiers in Oral Health, 2024)
Background: Betel Quid (BQ) chewing is a prevalent habit in Asia and the Pacific regions. It is deeply intertwined within cultural customs and has been reported to result in oral potentially malignant disorders (OPMD) and malignant disorders (MD). Objective: We aim to present a summative and broad overview of the burden BQ chewing has imposed on residents of the Southeast Asia, Pacific Islands and Australasia regions, allowing us to quantify the level of impact it is currently causing on people's risk of oral cancer. Methods: This scoping review and meta-analysis screened databases including PubMed, MEDLINE and Google Scholar, for publications that investigated the association between BQ and OPMD and MD.The search strategy involved MeSH headings relating to betel quid, OPMD and MD, and to search for results from January 2010 to June 2023 within set geographical boundaries of South-east Asian and Pacific regions. This systematic review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement for Scoping Reviews (PRISMAScR), R software was used to screen outliers. The included studies were further analyzed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. Results: 9 articles (n= 19,312 participants) which presented odds ratio outcomes from 11 regionally different study groups. We indicated a strong correlation between BQ chewing and the increased risk of OMPD and MD. The risk was quantified through meta-analyses with OR 8. 18 [5.27; 12.72] and increased when outlier was removed, OR 9. 93 [7.36; 13.39]. BQ chewing was further identified within various Australian communities and discovered to be produced locally in North Queensland. Discussion: metaanalysis of 2 outcomes had substantial heterogeneity and minor evidence of publication bias, thus effect was included with and without these articles. The overall GRADE quality of evidence ranged from moderate to very high and highlighted 5 studies with serious imprecision. Conclusion: The lingering high prevalence of BQ in the SEA and Pacific regions as well as its rising acceptance among non-ethnic Australians is alarming and requires prompt and rigorous intervention to prevent risk of oral cancer.The review protocol was registered to PROSPERO (Ref: CRD42023429694).